BRITISH COUNCIL LEARNENGLISH KIDS AS ASYNCHRONOUS LEARNING TO IMPROVE YOUNG LEARNERS’ WRITING - Dian Dwi Lestari; Puspa Dewi; Edi Sunjayanto Masykuri (Universitas Muhammadiyah Metro, 2026)
To improve the English writing abilities of fifth-grade primary school students in Kebumen Regency, Indonesia, this study examines the efficacy of using the British Council for Kids application within a deep learning-based Mobile Assisted Language Learning (MALL) in asynchronous learning model. This study used a pre-experimental one-group pretest-posttest design using a quantitative methodology. A cluster sampling strategy was used to choose 74 kids as participants. A pre-test, two therapy sessions with activities from the British Council for Kids, independent practice, a post-test, and a perception questionnaire made up the four-week intervention. A Paired t-test and N-gain score computation using SPSS were used for statistical data analysis. The mean score increased significantly from 65.95 in the pre-test to 87.97 in the post-test. The mean score rose from 65.95 in the pre-test to 87.97 in the post-test, signifying a significant enhancement in students' writing proficiency. The N-gain analysis showed a mean score of 0.6371, indicating moderate efficacy. In conclusion, including the British Council for Kids into a MALL-based deep learning paradigm successfully improves writing abilities and cultivates a love of learning. To give young students more interesting and fulfilling educational experiences, the study promotes the use of MALL platforms in English classes. REFERENCES Agyeman, N. Y. B. (2024). Deep learning in high schools: Exploring pedagogical approaches for transformative education. Humanika, 24(2), 111–126. https://doi.org/10.21831/hum.v24i2.71350 Alhadiah, A. (2023). Undergraduate EFL learners’ use and acceptance of mobile-assisted language learning: A structural equation modeling approach. World Journal of English Language, 13(3), 253. https://doi.org/10.5430/wjel.v13n3p253 Alnujaidi, S. (2021). Adoption of mobile assisted language learning (MALL) in Saudi Arabian EFL classrooms. Journal of Language Teaching and Research, 12(2), 312. https://doi.org/10.17507/jltr.1202.13 Al-Shehab, M. A.-S. (2020). The role of mobile-assisted language learning (MALL) in enhancing the writing skills of intermediate IEP students: Expectations vs reality. Language Teaching Research Quarterly, 20, 1–18. https://doi.org/10.32038/ltrq.2020.20.01 Ambarita, J., Purnamasari, U., & Siahaya, A. (2025). Deep learning as a pathway to pedagogical transformation in Indonesia. Jurnal Penelitian Kebijakan Pendidikan, 18(1). https://doi.org/10.24832/jpkp.v18i1.1229 Anasta, A. P., & Dharmawan, Y. Y. (2025). Enhancing descriptive writing through semantic mapping and STAD: A quasi-experimental study in Indonesian EFL. Scripta : English Department Journal, 12(2), 335–345. https://doi.org/10.37729/scripta.v12i2.7013 Andayanie, L. M., Adhantoro, M. S., Purnomo, E., & Kurniaji, G. T. (2025). Implementation of deep learning in education: Towards mindful, meaningful, and joyful learning experiences. Journal of Deep Learning, 47–56. Aryana, S., Sobari, T., Wikanengsih, Fauziya, D. S., & Mustika, R. I. (2025). The effectiveness of 21st century competency assessment model and HOTS inimproving writing skills: An experimental research. Journal of Language Teaching and Research, 16(4), 1115–1128. https://doi.org/10.17507/jltr.1604.07 Asadi, S. S. A., & Al-Issa, N. (2022). Using online platforms to improve writing. Journal of the College of Education for Women, 33(2), 43–54. https://doi.org/10.36231/coedw.v33i2.1587 Asfarini, D., Basuki, B., Wan, A. T., & Masykuri, E. S. (2024). Review study learning apps in teaching vocabulary using duolingo. Scripta : English Department Journal, 11(1), 48–56. https://doi.org/10.37729/scripta.v11i1.3836 Asrial, A., Syahrial, S., Kurniawan, D. A., Subandiyo, M., & Amalina, N. (2019). Exploring obstacles in language learning among prospective primary school teacher. International Journal of Evaluation and Research in Education (IJERE). Bakri, U. (2023). Utilizing mobile-assisted language learning (mall) to enhance student's writing skills. EDISI: Jurnal Edukasi dan Sains https://ejournal.stitpn.ac.id/index.php/edisi Barton, G., Khosronejad, M., Ryan, M., Kervin, L., & Myhill, D. (2024). Teaching creative writing in primary schools: A systematic review of the literature through the lens of reflexivity. The Australian Educational Researcher, 51(4), 1311–1330. https://doi.org/10.1007/s13384-023-00641-9 Brookhart, S. M., & McMillan, J. H. (2019). Classroom Assessment and Educational Measurement (1st ed.). Routledge. https://doi.org/10.4324/9780429507533 Darsih, E., & Asikin, N. A. (2020). Mobile assisted language learning: EFL learners’ perceptions toward the use of mobile applications in learning English. English Review: Journal of English Education, 8(2), 183–194. https://doi.org/10.25134/erjee.v8i2.2999 Dwigustini, R., Sari, N., Susilawati, S., & Nisa, B. (2021). Fostering studentsâ€TM writing skill by the integration of MALL application. JOLLT Journal of Languages and Language Teaching, 9(1), 34–43. https://doi.org/10.33394/jollt.v9i1.3264 Ebrahimi, S. S. (2024). Effects of mobile messaging applications on writing skill. Ampersand, 13, 100209. https://doi.org/10.1016/j.amper.2024.100209 Gatlabayan, M. (2024). Enhancement of students’ English vocabulary skills through a mobile assisted language learning (Mall) app. Journal of Higher Education Research Disciplines, 9(1), 14–31. Harmanto, M. (2021). The influence of mall on enhancing studentsâ€TM literacy skills. Premise: Journal of English Education, 10, 88. https://doi.org/10.24127/pj.v10i1.3566 Hasanah, N., & Rahman, B. I. (2025). Educaplay for high school students in improving writing skills: A teacher’s perspective. Scripta : English Department Journal, 12(1), 85–100. https://doi.org/10.37729/scripta.v12i1.6398 Hawamdeh, M., & Soykan, E. (2021). Systematic analysis of effectiveness of using mobile technologies (MT) in teaching and learning foreign language. Online Journal of Communication and Media Technologies, 11(4), e202124. https://doi.org/10.30935/ojcmt/11256 Keezhatta, M. S., & Omar, A. (2019). Enhancing reading skills for saudi secondary school students through mobile assisted language learning (MALL): An experimental study. International Journal of English Linguistics, 9(1), 437. https://doi.org/10.5539/ijel.v9n1p437 Khashan, H. S., & AbuSeileek, A. F. (2023). The effect of using british council BBC learning English application on the tenth grade EFL students’ listening and speaking skills and their attitudes toward it. Krisbiantoro, B., & Pujiani, T. (2021). The effectiveness of MALL and flipped classroom in teaching writing to the eleventh graders of SMA in Banyumas. EduLite: Journal of English Education, Literature and Culture, 6(1), 86. https://doi.org/10.30659/e.6.1.86-104 Masykuri, E. S., Alekseevna, K. E., & Nugraeni, I. I. (2025). Designing asynchronous digital media for teaching reading comprehension by implementing task-based learning. Journal of Education and Teaching (JET), 6(1), 109–125. https://doi.org/10.51454/jet.v6i1.485 Masykuri, E. S., Vlаdimirоvnа, V. O., & Evgenevichc, M. I. (2023). First-year-students’ perceptions of asynchronous media platform (AMP) for learning English. English Language Teaching Educational Journal, 6(3), 188–198. https://doi.org/10.12928/eltej.v6i3.6661 Maulana, A. H., Putra, A. S., & Rohim, A. (2024). Optimizing english language training through british council learn english kids in banthamaprao school thailand. | LOSARI: Jurnal Pengabdian Kepada Masyarakat. https://ojs.losari.or.id/index.php/losari/article/view/401 Muslem, A., Kasim, U., Mustafa, F., Fitriani, S. S., & Rahmi, M. (2024). The correlation between the use of online learning platforms and undergraduate students’ self-efficacy. Journal of Language and Education, 10(1), 83–100. https://doi.org/10.17323/jle.2024.17606 Nadila, Y., & Widiastuti, O. (2025). Students’ vocabulary mastery. 14. https://doi.org/10.33373/dms.v14i2.7742 Nasution, U. A., Dewi, U., & Daulay, S. H. (2023). Students’ perception of using mobile assisted language learning (MALL) as a media for learning english. Conference on English Language Teaching, 951–958. Peng, H., Jager, S., & Lowie, W. (2021). Narrative review and meta-analysis of MALL research on L2 skills. ReCALL, 33(3), 278–295. https://doi.org/10.1017/S0958344020000221 Pingmuang, P., & Koraneekij, P. (2022). Mobile-assisted language learning using task-based approach and gamification for enhancing writing skills in EFL students. Electronic Journal of E-Learning, 20(5), 623–638. https://doi.org/10.34190/ejel.20.5.2339 Pratiwi, V. U., Nurkamto, J., & Anindyarini, A. (2022). Writing skills for primary students: need analysis to implement the scientific approach. Educational Research. Putri, S. A., Amri, S., & Ahmad, A. (2020). The students’ difficulties factors in speaking. J-Shelves of Indragiri (JSI), 1(2), Article 2. https://doi.org/10.32520/jsi.v1i2.1059 Rahman, Md. M., Tabash, M. I., Salamzadeh, A., Abduli, S., & Rahaman, Md. S. (2022). Sampling techniques (probability) for quantitative social science researchers: a conceptual guidelines with examples. SEEU Review, 17(1), 42–51. https://doi.org/10.2478/seeur-2022-0023 Rao, 2019. (n.d.). Retrieved November 9, 2025, from https://www.researchgate.net/profile/Parupalli-Rao/publication/334282978_THE_ROLE_OF_ENGLISH_AS_A_GLOBAL_LANGUAGE/links/5d21b86e299bf1547c9effdb/THE-ROLE-OF-ENGLISH-AS-A-GLOBAL-LANGUAGE.pdf Sari, D. D. (2021). | The correlation between students’ vocabulary achievement and fluency in speaking english. English Teaching and Linguistics Journal (ETLiJ), 2(1), Article 1. https://doi.org/10.30596/etlij.v2i1.5507 Seroja Br Ginting, R., & Fithriani, R. (2021). Using the hello English application in the EFL classroom: Its efficacy in helping students to master vocabulary. KnE Social Sciences, 592–600. https://doi.org/10.18502/kss.v5i4.8714 Sihombing, A. H. I., & Ismahani, S. (2025). Students’ perception of using british council learn english for increasing vocabulary acquisition. Sosioedukasi : Jurnal Ilmiah Ilmu Pendidikan dan Sosial, 14(1), 290–302. https://doi.org/10.36526/sosioedukasi.v14i1.5409 Sukmawati, D., Sunjayanto, E., & Triana, J. (2025). An asynchornous learning to improve vocabulary building by using Youtube channel. Scripta : English Department Journal, 12(1), 164–173. https://doi.org/10.37729/scripta.v12i1.6331 Sunjayanto Masykuri, E. (2022). Technology effect of EFL listening comprehension to teacher during pandemic. Journal of English Teaching and Learning Issues, 5(1), 51. https://doi.org/10.21043/jetli.v5i1.13913 Vicol, M.-I., Gavriluț, M.-L., & Mâță, L. (2024). A quasi-experimental study on the development of creative writing skills in primary school students. Education Sciences, 14(1), 91. https://doi.org/10.3390/educsci14010091 Wu, X.-Y. (2024). Exploring the effects of digital technology on deep learning: A meta-analysis. Education and Information Technologies, 29(1), 425–458. https://doi.org/10.1007/s10639-023-12307-1 Xiaoli, Y. (2024). Enhancing early language learning: The impact of mobile-assisted language learning (MALL) on young learners’ language proficiency. Occupation and Professional Education, 1(5), 71–76. https://doi.org/10.62381/O242512 Yucedal, H. M. (2023). Integrating mobile assisted language learning (MALL) into EFL classes at a tertiary level. Revista Amazonia Investiga, 12(62), 92–104. https://doi.org/10.34069/AI/2023.62.02.7 Zalani, M., Weisi, H., & Yousofi, N. (2024). The influence of mobile-assisted critical writing instructions on EFL learners’ writing skill in language institutes. Frontiers in Education, 9, 1465765. https://doi.org/10.3389/feduc.2024.1465765 Zaniar, S., Djuwari, Afandi, M. D., Aquariza, N. R., & Authar, N. (2025). Enhancing writing proficiency through mobile-assisted language learning (mall): insights and innovations. English Language Teaching Methodology, 5(1), 31–42. https://doi.org/10.56983/eltm.v5i1.1757